Avian Infectious Bronchitis Virus: Molecular Detection in Southwestern Ethiopia Chickens - Bezina Arega Emeru; Haregawi Tesfaye Desta (International Journal of Microbiology)
Infectious bronchitis virus (IBV) is a significant threat to poultry worldwide, but its status in Ethiopia remains understudied. Thus, this study aimed to detect the virus and associated risk factors in South West Ethiopia. Ninety oropharyngeal swab samples were purposively collected from symptomatic chickens located in Jimma town, Seqa Chekorsa, and Tiro Afeta woredas of the Jimma zone between November 2021 and April 2022 to detect IBV virus by using RT-PCR. A side-by-side questionnaire was administered to assess risk factors. Total RNA was extracted, reverse transcription polymerase chain reaction (RT-PCR) was conducted, and products were visualized under UV light. The overall proportion of IBV was 16.6% (15/90). No statistical association was observed between any of the animal risk factors and the detection of the virus (P=0.57, 0.586, and 1). However, the proportion of birds infected by the virus was higher in males, exotic breeds, and adults compared to females, local breeds, and young birds. Similarly, none of the management risk factors had a significantly different effect on virus detection (P=0.25, 0.09, 0.088, and 0.726). However, improper carcass disposal (OR = 0.43, 95% CI: 0.13–1.4), lack of veterinary services (OR = 2.7, 95% CI: 0.8–8.3), and the presence of wild birds/rodents (OR = 4.4, 95% CI: 0.88-22.3) were associated with increased IBV risk but not cleaning of feeders/drinkers (OR = 1.1, 95% CI: 0.2–4.8). These findings underscore the need for enhanced biosecurity practices and further research to implement informed IBV control strategies in Ethiopia.